Repurposed ciprofloxacin derivatives as potent autophagic-type anticancer agents - Gone, Nilu Vijay; Sharma, Tanisha; Joshi, Rakesh; Upreti, Akshita; Santra, Manas; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2026)
Drug repurposing - also known as drug repositioning is a proven strategy for identifying new therapeutic uses for existing and pre-approved drugs with considerable success in recent years. Herein, we report the discovery of a novel class of ciprofloxacin-amino acid conjugates that are dynamically potent against different cancer cell lines. Some of the molecules reported herein displayed a strong anti-proliferative effect on MCF-7 (IC50: 6 mu M). The most active anti-proliferative molecule of this series 7a suppressed the proliferation of HCT116, A549, and MDAMB-231 cancer cell lines. Furthermore, we established that the treatment with 7a leads to DNA damage-mediated autophagic cell death in cancer cells. Our findings suggest that appropriate derivatization of the ciprofloxacin drug can yield promising anti-cancer compounds in easy synthetic operations.
Keywords: Anticancer drugs; Autophagic cell death; ciprofloxacin